APLIKASI ORDERING INTERIOR AND EXTERIOR RUMAH PADA CV. ALTRA PRATAMA BERBASIS ANDROID - saleh Dwiyatno; Edy Rakhmat; Ayu Purnama Sari; Zanuandry Zanuandry (Jurnal Sistem Informasi dan Informatika (Simika), 2020)
This research was conducted at CV.Altra Pratama with the aim to design a system to help the CV.Altra Pratama in an effort to expand sales millionaires and facilitate consumers in purchasing. Previously they still used conventional methods or customers came directly to the store, so to make it easier in the transaction is made an application system ordering interior and exterior homes in CV.Altra Pratama, in order to maximize sales and marketing. In this study using an Android-based programming language and for terms of writing using the prototype method. This making uses Android Studio version 3.0.2 and Android SDK as API tools. Application made with java and XML programming languages.